(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
Camels ( Camelus dromedarius ) in the Sudan act as intermediate host for many species of cyst forming coccidian parasites . Oocysts of Toxoplasma gondii , Cystoisospora felis and Cystoisospora rivolta were isolated from cats experimentally fed infected camel meat while sporocysts of Sarcocystis cameli , Sarcocystis spp. and oocysts of Hammondia hedorni , Cystoisospora ohieonsis and Cystoisospora burrowsi were isolated from dogs . Studies on Toxoplasma and Sarcocystis that were carried on camels in Sudan were discussed .